2022
DOI: 10.1101/2022.09.29.510234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biomass generation and heterologous isoprenoid milking from engineered microalgae grown in anaerobic membrane bioreactor effluent

Abstract: Wastewater (WW) treatment in anaerobic membrane bioreactors (AnMBR) is considered more sustainable than in their aerobic counterparts. However, outputs from AnMBR are mixed methane and carbon dioxide gas streams as well as ammonium- (N) and phosphate- (P) containing waters. Using AnMBR outputs as inputs for photoautotrophic algal cultivation can strip the CO2 and remove N and P from effluent which feed algal biomass generation. Recent advances in algal engineering have generated strains for concomitant high-va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…As alternatives to fermentative hosts, algal chassis can produce heterologous products of interest directly from CO 2 as a carbon source, while consuming nitrogen and phosphorous sources in water (de Freitas et al, 2023). These properties make microalgae interesting for sustainable bio-production concepts that convert waste to value.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As alternatives to fermentative hosts, algal chassis can produce heterologous products of interest directly from CO 2 as a carbon source, while consuming nitrogen and phosphorous sources in water (de Freitas et al, 2023). These properties make microalgae interesting for sustainable bio-production concepts that convert waste to value.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently shown that heterologous patchoulol production was lower when cells were exposed to modeled higher temperature and light environmental conditions (de Freitas et al, 2023), suggesting that both temperature and light regimes impact isoprenoid biosynthesis in the alga. Isoprene synthases have optimal catalytic activities at ∼42 °C (Li et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most desert countries have coastal regions, including the Arabian Peninsula, Northern Australia, Chile, and North Africa (Lefers et al, 2020;Greene et al, 2022). At these locales, saline microalgal processes are logical (Ishika et al, 2017), and inland, where human settlements occur, freshwater algal cultivation can participate in waste-water treatment and reuse (de Freitas et al, 2023). It was recently reported that the geographical areas with the highest potential for onshore marine microalgae biomass production were between 30°N and 30°S in the so-called "hot belt countries" (Greene et al, 2022).…”
Section: Introductionmentioning
confidence: 99%